Three Es of linked injury data: Episodes, Encounters and Events. Issue 5 (28th April 2021) - Vallmuur, Kirsten; McCreanor, Victoria; Cameron, Cate; Watson, Angela; Shibl, Rania; Banu, Shahera; McPhail, Steven M; Warren, Jacelle
Abstract : Background: Treatment and recovery times following injury can be lengthy, comprising multiple interactions with the hospital system for initial acute care, subsequent rehabilitation and possible re-presentation due to complications. Aims: This article aims to promote the use of consistent terminology in injury data linkage studies, suggest important factors to consider when managing linked injury data, and encourage thorough documentation and a robust discourse around different approaches to data management to ensure reproducibility, consistency and comparability of analyses arising from linked injury data. Approach: This paper is presented in sections describing: (1) considerations for identifying injury cohorts, (2) considerations for grouping Episodes into Encounters and (3) considerations for grouping Encounters into Events. Summary tools are provided to aid researchers in the management of linked injury data. Discussion: Careful consideration of decisions made when identifying injury cohorts and grouping data into units of analysis (Episodes/Encounters/Events) is essential when using linked injury data. Choices made have the potential to significantly impact the epidemiological and clinical findings derived from linked injury data studies, which ultimately affect the quality of injury prevention initiatives and injury management policy and practice. It is intended that this paper will act as a call to action for injury linkage methodologists, and those using linked data, to critique approaches, share tools and engage in a robust discourse to further advance the use of linked injury data, and ultimately enhance the value of linked injury data for clinicians and health and social policymakers.